Using non-insecticidal traps indoors can complement insecticide-treated nets to target insecticide-resistant malaria vectors - Romaric Akoton; Pierre Marie Sovegnon; Oswald Y. Djihinto; Adandé A. Medjigbodo; Romuald Agonhossou; Ayola Akim Adegnika; Gabriella Gibson; Rousseau Djouaka; Frances M. Hawkes; Luc S. Djogbénou (Parasites & Vectors)
Abstract Background Insecticide-treated nets (ITNs) provide protection against malaria vectors through their insecticidal action and as a physical barrier. However, insecticide resistance in malaria vectors has diminished their efficacy, threatening future malaria control. To reinforce ITNs’ effectiveness, evaluating non-insecticide-based tools in an integrated control approach is worthwhile. In the present study, a mosquito collection technique, the Host Decoy Trap (HDT), was coupled with standard ITNs as a complementary intervention, and its effectiveness against insecticide-resistant Anopheles gambiae s.l. was assessed in experimental huts. Methods An HDT combined with either permethrin or deltamethrin-treated nets was tested against field-collected An. gambiae mosquitoes from Za-Kpota (Benin Republic) in experimental hut trials following WHO Phase II guidelines. Effectiveness was assessed in terms of mosquito mortality, blood feeding and exophily rates. Prior to hut trials, an insecticide susceptibility test was performed on field-collected An. gambiae s.l. mosquitoes to screen for pyrethroid resistance. Results A significantly higher mortality rate was observed against both susceptible and field-collected An. gambiae s.l. mosquitoes when ITNs were used with HDT (ranging from 80.18 to 99.78%) compared to alone (2.44–100%). The combined use of treated nets with HDT resulted in a lower rate (ranging from 0 to 10.83%) of blood feeding compared to the treated nets alone (ranging from 0 to 16.93%). When treated nets were hung next to the HDT, they significantly limited the number of insecticide-resistant mosquitoes that exited experimental huts compared to the nets alone. Conclusions The use of HDT alongside ITNs has been demonstrated to significantly reduce the likelihood of vector-host contact by insecticide-resistant An. gambiae. A combination of HDT and treated nets reduced the number of live An. gambiae mosquitoes as well as the blood-feeding rate. Furthermore, it reduced the number of mosquitoes likely to leave the huts and enter the natural environment. Altogether, our findings highlight the potential of integrated approaches combining non-insecticidal trapping devices with ITNs when designing future integrated vector control strategies.